The Impact of Road Section Damage on Alternative Transportation Routes: A Systematic Literature Study - Iip Faturohman; Andi Nugraha Saputra; Mushthofa; Asep Dian Heryadiana; Muhammad Isradi (LEADER: Civil Engineering and Architecture Journal, 2025)
This study examined the effect of road damage on the operation of alternate transportation routes using the systematic literature review (SLR) method. This study focused on the impact of road geometry, various forms of road damage, and societal repercussions. Major academic databases were searched for literature from 2013 to 2023 using the predetermined inclusion and exclusion criteria. According to general studies, geometric elements, including lane width, curvature, slope, and shoulder conditions, are directly associated with different types of damage, such as cracks, potholes, grooves, and drainage failures. These damages result in decreased route capacity, longer delivery times, higher rates of vehicle damage, higher accident risks, and restricted access to essential services. The social effects are substantial in places with little redundancy in the infrastructure. The findings demonstrate the importance of integrated planning that takes preventative maintenance and geometric design into account to guarantee transportation resilience and community welfare.